Pengaruh Beban Kerja, Perilaku Karyawan, Iklim Organisasi dan Job Deskripsi Terhadap Kinerja Karyawan Dengan Motivasi sebagai Variabel Moderasi - Widiyanto, Hendy; Nurul Hidayat; Shine Pintor Siolemba Patiro (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to determine and analyze the effect of workload on employee performance, the effect of employee behavior on employee performance, the effect of organizational climate on employee performance, the effect of job description on employee performance, the effect of motivation on employee performance, the effect of workload on employee performance in motivation moderation, the effect of employee behavior on employee performance in motivation moderation, the effect of organizational climate on employee performance in motivation moderation and the effect of job description on employee performance in motivation moderation. The research method used is quantitative research with a survey method. The research instrument is a questionnaire for employees of PT. Bulir Emas Nusantara (BEN) in Karawang Regency. The sample in this study was 97 employees of PT. Bulir Emas Nusantara (BEN). The data analysis technique uses SEM-PLS (Structural Equation Modeling Partial Least Square) Smart PLS 3.2.7 to test the nine hypotheses proposed in this study. The results of the study indicate that workload has a significant positive effect on employee performance, employee behavior has a positive but insignificant effect on employee performance, organizational climate has a negative but insignificant effect on employee performance, job description has a significant positive effect on employee performance, motivation has a significant positive effect on employee performance, workload has a positive but insignificant effect on employee performance in motivation moderation, organizational climate has a positive but insignificant effect on employee performance in moderation. Conclusion Motivation does not moderate workload, employee behavior, organizational climate and job description on employee performance. Keywords: Employee Behavior, Organizational Climate, Job Description, Motivation